2021
DOI: 10.1177/15330338211011961
|View full text |Cite
|
Sign up to set email alerts
|

S100A11 Promotes Glioma Cell Proliferation and Predicts Grade-Correlated Unfavorable Prognosis

Abstract: The prognosis of glioma is significantly correlated with the pathological grades; however, the correlations between the prognostic biomarkers with pathological grades have not been elucidated. S100A11 is involved in a variety of malignant biological processes of tumor, whereas its biological and clinicopathological features on glioma remain unclear. In this study, the S100A11 expression and clinical information were obtained from the public databases (TCGA, GEPIA2) to analyze its correlations with the patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…S100A11 is a member of the S100 family, which exerts its biological functions as a calcium sensor or binding protein [ 24 ]. Recently, studies have found that, the expression of S100A11 is positively correlated with the degree of cancer progression and an unfavourable clinical prognosis [ 13 , 25 , 26 ]. Silencing of S100A11 in intrahepatic cholangiocarcinoma can reduce the level of SMAD2/3 phosphorylation which is induced by TGF-β1, and then inhibit cell migration, invasion and epithelial-mesenchymal transition (EMT) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…S100A11 is a member of the S100 family, which exerts its biological functions as a calcium sensor or binding protein [ 24 ]. Recently, studies have found that, the expression of S100A11 is positively correlated with the degree of cancer progression and an unfavourable clinical prognosis [ 13 , 25 , 26 ]. Silencing of S100A11 in intrahepatic cholangiocarcinoma can reduce the level of SMAD2/3 phosphorylation which is induced by TGF-β1, and then inhibit cell migration, invasion and epithelial-mesenchymal transition (EMT) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third way is metastasis through the lymphatic system. Glioma can also metastasize through the lymphatic system, and tumors may enter specific organs or parts of the body along the lymphatic space around spinal nerves or cranial nerves to induce diseases [ 5 ]. Because all parts of the body are lymphatic, this metastasis is very harmful to the body.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most fundamental features of gliomas, abnormal proliferation can lead to continuous tumor progression, crowding out the viability of normal brain tissue and leading to immature differentiation of neoplastic cells, further aggravating the malignancy of gliomas (Caglayan et al 2013 ). It has been reported that expression of S100A11, which correlates with glioma pathological grade, promotes the proliferation and tumorigenic capacity of glioma cells, and knockdown of S100A11 expression using shRNA results in the opposite phenotype (Wang et al 2021 ). Similarly, knockdown of DRAXIN was demonstrated in this experiment to significantly inhibit the proliferative capacity of U251 cells.…”
Section: Discussionmentioning
confidence: 99%